2022
DOI: 10.4314/sajas.v51i5.2
|View full text |Cite
|
Sign up to set email alerts
|

Sprinkler flow rate affects physiological, behavioural and production responses of Holstein cows during heat stress

Abstract: Holstein Friesian cows are known for their high milk yield. They are popular in the commercial dairy  sector of Pakistan. Heat stress is a major challenge for these animals owing to the longer summer season with high ambient temperatures (35 - 40 °C) and relative humidity (30 - 50%) in the area (Butt et al., 2020). Mitigating the effects of heat stress requires substantial investments in energy and water. Spraying dairy  cows with water in the holding pen or at the feed bunk is common practice as it lowers  bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Each CS lasted for 1 h with a 12 min cycle with 3 min water on and 9 min off. The sprinkler flow rate of 1.25 L/min was used as it efficiently cooled buffaloes [ 4 ] and Holstein Friesian cows [ 11 ]. The experiment lasted for two months (August and September 2019) with a one-week adaptation period.…”
Section: Methodsmentioning
confidence: 99%
“…Each CS lasted for 1 h with a 12 min cycle with 3 min water on and 9 min off. The sprinkler flow rate of 1.25 L/min was used as it efficiently cooled buffaloes [ 4 ] and Holstein Friesian cows [ 11 ]. The experiment lasted for two months (August and September 2019) with a one-week adaptation period.…”
Section: Methodsmentioning
confidence: 99%
“…This is supported by the observed improvements in core body temperatures and respiration rate, all of which are important indicators of animal welfare and productivity. Whilst the difference in respiratory rate between the treatment groups was not substantial, it closely aligned with rates reported in previous studies conducted under similar conditions (Bah et al ., 2021a, 2021b, 2022). Unlike cattle, buffaloes do not primarily rely on respiratory rate as a means to dissipate heat, instead, they employ wallowing behaviour, which facilitates heat dissipation through convection.…”
Section: Discussionmentioning
confidence: 99%
“…In semi-arid summer, cows cooled with 1.25 and 2.0 l/min flow rates produced similar physiological and productive responses (Bah et al ., 2021a; Macavoray et al ., 2023). While relatively limited research has been conducted on dairy buffaloes, a recent study showed that sprinklers with flow rates of 1.25 and 2.0 l/min resulted in similar physiological and productive responses in buffaloes (Bah et al ., 2021b). Further research in this area could lead to a better understanding of the efficiency of sprinkler cooling in buffaloes, particularly in relation to sprinkler cycles and flow rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that flow rates of 1.3 L per minute or higher have a similar effect on cow cooling [10]. A recent study research suggests that flow rates of 2 L per minute or 1.25 L per minute produce a similar effect on cow performance [11]. Spray frequency (cycles) also plays a role in cooling efficiency, as it depends on the duration of the spray (i.e., time water on) and the interval Sustainability 2023, 15, 3774 2 of 16 between sprays when the coat is allowed to dry (time off).…”
Section: Introductionmentioning
confidence: 99%